2005
DOI: 10.1080/02844310510006268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sildenafil citrate on viability of flaps: An experimental study in rats

Abstract: Various pharmacological agents have been used to try and elucidate the pathophysiology of ischaemia and necrosis of flaps. Their most important disadvantage is the need for relatively high doses given systemically, which increases the risk of potential side effects. Topical or local agents are more useful. Sildenafil citrate, the specific inhibitor of cyclic guanosine monophosphate (cGMP)-specific phosphodiesterase type 5 (PDE 5) was studied as an antianginal drug during the late 1980s, but is now used for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Numerous therapeutic agents have been and continue to be developed for the purpose of selectively increasing tissue blood flow to under-perfused tissue units. In several animal models of tissue ischemia, therapy employing L-arginine, cGMP phosphodiesterase inhibitors, or NO donors has increased tissue survival [111][112][113][114][115][116][117][118]. Since we have identified TSP1 as a major physiological regulator of NOsignaling in vascular cells, we investigated whether TSP1 could likewise regulate tissue blood flow.…”
Section: Tsp1 and Tissue Blood Flow And Survivalmentioning
confidence: 99%
“…Numerous therapeutic agents have been and continue to be developed for the purpose of selectively increasing tissue blood flow to under-perfused tissue units. In several animal models of tissue ischemia, therapy employing L-arginine, cGMP phosphodiesterase inhibitors, or NO donors has increased tissue survival [111][112][113][114][115][116][117][118]. Since we have identified TSP1 as a major physiological regulator of NOsignaling in vascular cells, we investigated whether TSP1 could likewise regulate tissue blood flow.…”
Section: Tsp1 and Tissue Blood Flow And Survivalmentioning
confidence: 99%
“…Conversely, Ayyildiz et al 7 reported the daily use of sildenafil subdermally, even though the type of restraint was not described.…”
Section: Resultsmentioning
confidence: 99%
“…On the distal third, however, there was a tendency to develop less granulation tissue in flaps treated with sildenafil ( Table 2). Ayyildiz et al 7 , which also applied it subdermally and was not increased due to the systemic response leading to the death of three animals in the study group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This antioxidant compound prevent lipid oxidation in food and prevent free-radicalinduced diseases such as aging caused by oxidative tissue degeneration, atherosclerosis and cancer, [6]. Sildenafil citrate, considered a specific inhibitor of cyclic guanosine monophosphate (cGMP)-specific phosphodiesterase type-5 (PDE-5), causes dilation of the peripheral veins and arteries due to enhanced nitric oxide (NO) synthesis [7], so used for treatment of erectile dysfunction. Several studies investigated the lipid peroxidation inhibition by cGMP analogues and cyclic adenosine Green Master Mix (QIAGEN Science, Maryland, USA), and nuclease-free water to a total volume of 20 μl.…”
Section: Introductionmentioning
confidence: 99%